The Effectiveness of Coconut Fiber Air Filtration in Reducing PM2.5 and PM10 in the Home Industry of Sago Craftsmen in Jaya Village, Tidore Islands City - Susan Arba; Herwin A Hi Adam (Poltekkes Kemenkes Tanjung Karang, 2025)
Particulate Matter (PM) is a dangerous pollutant of various sizes that can be detrimental to health, through penetration of the respiratory tract and entering the bloodstream. The sago industry (home industry scale) located in residential areas causes health problems, such as shortness of breath, dizziness and headaches. The study aims to analyze the effectiveness of air filtration made from coconut fiber to reduce particulates in the air (PM2.5 and PM10). The study used a one group pre-post test design, conducted in seven sago industries (home industries) in Jaya Village, Tidore Islands City. Data processing used Bivariate analysis, which was carried out to see wood dust before and after treatment. Data analysis used Paired T-Test to assess differences in PM levels before and after treatment. The results showed a difference in PM 2.5 levels before and after treatment (P= 0.0001). Similarly, PM10 parameters also showed a significant difference (P = 0.007). Based on these results, coconut fiber air filters are effective in reducing PM 2.5 and PM10 concentrations.